The association between communication impairments and acquired alexithymia in chronic stroke patients. Issue 5 (27th May 2020) - Hobson, Hannah; Chiu, Evangeline Grace; Ravenscroft, Chloe; Partridge, Kate; Bird, Geoffrey; Demeyere, Nele
ABSTRACT: Introduction: Language dysfunction has recently been suggested to be one route to alexithymia, an impairment in recognizing and communicating one's own emotions. Neuropsychological evidence is needed to investigate the possibility that acquired language problems could underlie acquired alexithymia. Method: This project examined data from a large group of chronic stroke patients ( N = 118) to test whether self-reported or behavioral measures of language and communication problems were associated with alexithymia. We also examined the impact of hemisphere of damage on alexithymia. Results: We found no differences in alexithymia levels for patients with observed language impairments on brief tests of picture naming, comprehension, and reading vs unimpaired patients. However, self-reported communication difficulties were found to be associated with higher scores of alexithymia, even after controlling for depression and anxiety. Patients with left- versus right-hemisphere damage did not differ in their alexithymia scores. Conclusions: We found partial support for the language hypothesis of alexithymia. We discuss potential reasons for the discrepant findings between the self-report and objective language measures and suggest that self-report measures may be more sensitive to milder, more pragmatic language impairments, as opposed to the severe structural language impairments measured by the cognitive screening tests.